2013
DOI: 10.1007/s12032-013-0640-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific effect of gender on upper tract urothelial carcinoma outcomes

Abstract: The research is to evaluate the age-specific differential effects of gender on outcomes in patients with upper tract urothelial carcinoma (UTUC) treated with radical nephroureterectomy (RNU). Between August 1998 and October 2010, we retrospectively reviewed the data from 285 (67.7%) men and 136 (32.3%) women treated with RNU for UTUC at our two institutions. Kaplan-Meier survival estimates the age-specific effect of gender on cancer-specific survival (CSS). Cox proportional hazards regression analyses were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“…In Asia, one multicenter report (15) from Japan revealed that the number of males were 2.7 times that of females; in addition, a single institution's study (16) from Korea even reported that the males were nearly quadruple the females. In mainland China, one study from Guangzhou (17) also reported twice as many males as females; however, another patient population (18, 19) in Beijing revealed similar gender distribution such as ours.…”
Section: Discussionsupporting
confidence: 77%
“…In Asia, one multicenter report (15) from Japan revealed that the number of males were 2.7 times that of females; in addition, a single institution's study (16) from Korea even reported that the males were nearly quadruple the females. In mainland China, one study from Guangzhou (17) also reported twice as many males as females; however, another patient population (18, 19) in Beijing revealed similar gender distribution such as ours.…”
Section: Discussionsupporting
confidence: 77%
“…However, no significant association has been identified between gender and CSS when assessing the initial postoperative risk [2]. Other studies have suggested that women could have decreased CSS when stratifying gender analyses by age or smoking habits [22,23]. Our findings highlighted that, although gender did not have an impact on CSS at baseline, female sex was an independent risk factor of poorer long-term CSS rates in >3-yr survivors.…”
Section: Discussioncontrasting
confidence: 53%
“…61 Similarly, Tanaka et al 62 reported male gender, together with tumour multifocality and positive urinary cyto logy, as independent risk factors for intravesical recurrence. Liu et al 63 found an increased risk of death from UTUC in women ≥59 years old compared with men of the same age (P <0.001), whereas women aged 42-58 years (P = 0.011) and <42 years (P = 0.019) had better CSS than men ( Figure 2). …”
Section: Gender Differences In Utucmentioning
confidence: 95%